Underpricing Saham Perdana: Pengaruh Total Aset, ROA, dan DER - W, Nicole Kaylee; Dhia Wenny, Cherrya (MDP Student Conference, 2024)
The purpose of this study is to examine the influence of Total Asset, ROA, and DER on underpricing in the primary market at the Indonesia Stock Exchange (IDX) for the period 2019-2022. Data analysis was conducted using multiple linear regression methods. The study showed that only the total asset of the company had an influence on underpricing. Companies with high total assets of the company tend to experience higher underpricing. During the 2019-2022 period, this can be explained by the hot issue market. Knowing this market condition, investors are willing to pay more than the fair price for the company's shares. This study has important implications for companies that will conduct an IPO. Companies need to consider the factor of total assets of the company in determining the price of their initial shares.